PENINGKATAN PENGETAHUAN TENTANG KOSMETIK DAN ALAT KESEHATAN YANG AMAN DI SMKN 57 JAKARTA - Latirah; Rachmawati, Siti Rahayu; Suriawati, Junie (DHARMA BAKTI, 2021)
In modern times, people can easily find various types of cosmetics and medical devicesranging from cosmetics used to apply makeup, whiten faces, maintain body odor to safe andcomfortable ways to deal with menstrual periods. Most people buy cosmetics withoutknowing what content is contained in these cosmetics. Even though not all cosmetic-basedbrands are safe. As a form of practicing the Tri Darma of Higher Education, the HealthPolytechnic of the Ministry of Health Jakarta II Diploma III Pharmacy and Food AnalysisStudy Program carries out Community Service (PKM) activities with the aim of increasingawareness of the importance of selecting safe and correct cosmetics and medical devices forSMKN 57 students Jakarta. The method used in this community service activity is lectures.Activities are carried out online and follow-up activities are evaluation of activities andpreparation of activity reports. The results of the pre and post test showed that 40 studentsexperienced an increase in their post test scores, and each of 6 students experienced adecrease and no increase in their post test scores. However, this PKM provided an increasein students' knowledge of safe medical devices and cosmetics (p <0.05).